Towards a personalized risk assessment for exposure of humans to toxic substances - Thaís de Almeida Pedrete; Caroline de Lima Mota; Eline Simões Gonçalves; Josino Costa Moreira (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2016)
Abstract Great response variability caused by genetic and/or environmental factors has been observed among organisms exposed to hazardous chemicals. This subject has been a topic of intense discussion in the USA since President Obama announced support for an "era of precision medicine", which consists in the inclusion of genetic data of patients in the treatment design, imposing a new approach to risk assessment. Personalized evaluation must consider the phenotypic factors of an individual. Among the markers that have been developed to evaluate any alteration in the structure or function of organisms, biomarkers of susceptibility are of great importance because they indicate the natural characteristics of a given organism which make it more sensitive to a specific adverse effect or disease, or more responsive to exposure to a specific chemical/drug. The '-omics' technologies provide an insight into the relationship between chemical effects and molecular mechanisms of action. These technologies are the pillars for a personalized toxicology and precision medicine. Predictive toxicology requires a more comprehensive knowledge on specific individual factors or susceptibilities predisposing to diseases, enabling personalized risk assessment and adequate medical treatment.